Step * 1 1 1 of Lemma interleaving_singleton


1. Type
2. List@i
3. : ℕ||L||@i
4. L1 List
5. L2 List
6. f1 : ℕ||L1|| ⟶ ℕ||L||
7. f2 : ℕ||L2|| ⟶ ℕ||L||
8. interleaving_occurence(T;L1;L2;L;f1;f2)
9. ∀i@0:ℕ||L1||. ((f1 i@0) i ∈ ℤ)
10. ∀i@0:ℕ||L2||. ((f2 i@0) i ∈ ℤ))
11. ∀i@0:ℕ||L||
      (((i@0 i ∈ ℤ (∃j:ℕ||L1||. ((f1 j) i@0 ∈ ℤ))) ∧ ∃j:ℕ||L2||. ((f2 j) i@0 ∈ ℤsupposing ¬(i@0 i ∈ ℤ))
12. : ℕ||L1||
13. (f1 j) i ∈ ℤ
14. ∃j:ℕ||L2||. ((f2 j) i ∈ ℤsupposing ¬(i i ∈ ℤ)
⊢ L1 [L[i]] ∈ (T List)
BY
Assert 0 < ||L1|| }

1
.....assertion..... 
1. Type
2. List@i
3. : ℕ||L||@i
4. L1 List
5. L2 List
6. f1 : ℕ||L1|| ⟶ ℕ||L||
7. f2 : ℕ||L2|| ⟶ ℕ||L||
8. interleaving_occurence(T;L1;L2;L;f1;f2)
9. ∀i@0:ℕ||L1||. ((f1 i@0) i ∈ ℤ)
10. ∀i@0:ℕ||L2||. ((f2 i@0) i ∈ ℤ))
11. ∀i@0:ℕ||L||
      (((i@0 i ∈ ℤ (∃j:ℕ||L1||. ((f1 j) i@0 ∈ ℤ))) ∧ ∃j:ℕ||L2||. ((f2 j) i@0 ∈ ℤsupposing ¬(i@0 i ∈ ℤ))
12. : ℕ||L1||
13. (f1 j) i ∈ ℤ
14. ∃j:ℕ||L2||. ((f2 j) i ∈ ℤsupposing ¬(i i ∈ ℤ)
⊢ 0 < ||L1||

2
1. Type
2. List@i
3. : ℕ||L||@i
4. L1 List
5. L2 List
6. f1 : ℕ||L1|| ⟶ ℕ||L||
7. f2 : ℕ||L2|| ⟶ ℕ||L||
8. interleaving_occurence(T;L1;L2;L;f1;f2)
9. ∀i@0:ℕ||L1||. ((f1 i@0) i ∈ ℤ)
10. ∀i@0:ℕ||L2||. ((f2 i@0) i ∈ ℤ))
11. ∀i@0:ℕ||L||
      (((i@0 i ∈ ℤ (∃j:ℕ||L1||. ((f1 j) i@0 ∈ ℤ))) ∧ ∃j:ℕ||L2||. ((f2 j) i@0 ∈ ℤsupposing ¬(i@0 i ∈ ℤ))
12. : ℕ||L1||
13. (f1 j) i ∈ ℤ
14. ∃j:ℕ||L2||. ((f2 j) i ∈ ℤsupposing ¬(i i ∈ ℤ)
15. 0 < ||L1||
⊢ L1 [L[i]] ∈ (T List)


Latex:


Latex:

1.  T  :  Type
2.  L  :  T  List@i
3.  i  :  \mBbbN{}||L||@i
4.  L1  :  T  List
5.  L2  :  T  List
6.  f1  :  \mBbbN{}||L1||  {}\mrightarrow{}  \mBbbN{}||L||
7.  f2  :  \mBbbN{}||L2||  {}\mrightarrow{}  \mBbbN{}||L||
8.  interleaving\_occurence(T;L1;L2;L;f1;f2)
9.  \mforall{}i@0:\mBbbN{}||L1||.  ((f1  i@0)  =  i)
10.  \mforall{}i@0:\mBbbN{}||L2||.  (\mneg{}((f2  i@0)  =  i))
11.  \mforall{}i@0:\mBbbN{}||L||
            (((i@0  =  i)  {}\mRightarrow{}  (\mexists{}j:\mBbbN{}||L1||.  ((f1  j)  =  i@0)))
            \mwedge{}  \mexists{}j:\mBbbN{}||L2||.  ((f2  j)  =  i@0)  supposing  \mneg{}(i@0  =  i))
12.  j  :  \mBbbN{}||L1||
13.  (f1  j)  =  i
14.  \mexists{}j:\mBbbN{}||L2||.  ((f2  j)  =  i)  supposing  \mneg{}(i  =  i)
\mvdash{}  L1  =  [L[i]]


By


Latex:
Assert  0  <  ||L1||




Home Index